Peran Adipati-Adipati Mangkunegaran Dalam Pelestarian Kepurbakalaan Jawa Kuno (1853-1944) - Muhammad Faiz (PURBAWIDYA, 2024)
The dukes of Mangkunegaran have always been interested in Old Javanese heritage. As the leader of the area that contains Old Javanese artifacts and sites, there are several efforts to keep the memory of Old Javanese alive. This article explores the role of Mangkunegaran dukes, from Mangkunegara IV to Mangkunegara VII, in Old Javanese heritage. Historical research was conducted in this article. Various sources, such as letters, newspapers, magazines, and buildings were used in this research. It is known that each duke has undertaken different endeavors. Mangkunegara IV was quite active in Old Javanese history writing and artifact collecting. During the time of Mangkunegara V and VI, little was done due to the economic crisis. Mangkunegara VII supported Old Javanese archaeology activities due to his agenda of reconstructing Javanese society with the foundation of Java’s glorious past. This article is important to understand the role of the colonial era kingdom in heritage protection.